2018
DOI: 10.1016/j.amsu.2018.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Post hepatectomy liver failure – A comprehensive review of current concepts and controversies

Abstract: Post hepatectomy liver failure (PHLF) comprises of a conundrum of symptoms and signs following major hepatic resections. The pathophysiology essentially revolves around disruption of the normal hepatocyte regeneration and disturbed liver homeostasis. Prompt identification of the pre-operative predictors of PHLF in the form of biochemical parameters and imaging features are of paramount importance for any hepatic surgeon and forms the cornerstone of its management. Treatment revolves around a goal-directed resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 78 publications
1
72
0
1
Order By: Relevance
“…However, extended liver resection may lead to the development of progressive liver failure in the postoperative period which is associated with very high mortality rate. 103 Steatotic liver have poor ability to regenerate and reduced tolerance against ischemic injury. Therefore, patients with NAFLD are at higher risk of post-liver resection liver failure.…”
Section: Post-liver Resection Liver Failurementioning
confidence: 99%
“…However, extended liver resection may lead to the development of progressive liver failure in the postoperative period which is associated with very high mortality rate. 103 Steatotic liver have poor ability to regenerate and reduced tolerance against ischemic injury. Therefore, patients with NAFLD are at higher risk of post-liver resection liver failure.…”
Section: Post-liver Resection Liver Failurementioning
confidence: 99%
“…After a recovery period of 1-2 weeks, Stage 2 is performed in which the deportalized liver is removed to render the patient completely tumor-free [45]. Furthermore, HGF levels were found to be significantly elevated on PODs 1, 7, and 14 after living donor hepatectomy and were correlated with recipient liver volumes on POD 14 [11,[46][47][48][49][50][51][52][53][54][55]. Tomiya et al reported an association of serum HGF levels with hepatocellular dysfunction and systemic inflammation [56].…”
Section: Growth Factorsmentioning
confidence: 99%
“…This poses a marked morbidity and mortality risk for patients, and surgeons and clinicians should aim to ensure that postoperative liver failure does not occur. In clinical practice, there is a high variety of morphological and biochemical assessment methods for qualitative (indocyanine green retention rates; LiMAxtests, MELD or CHILD-PUGH scores) and quantitative (computed tomography liver volumetry, analysis of bilirubin, transaminases, albumin) predictions for liver function in the context of liver resection [11]. However, noninvasive individualized identification of valid predictive and prognostic biomarkers of PHLF based on the cytokines and hepatic growth factors in the liquid-biopsy samples might be a novel approach in the peri-operative diagnosis and monitoring of regeneration on a molecular basis.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic arterial buffer response, after reduction of portal blood flow post-PVE, can increase the size of the tumor. However, PVE preceded by trans-arterial chemoembolization (TACE) may prevent this by causing tumour necrosis [152] . RLE on Gd-EOB-DTPA-MRI has also been evaluated both pre-and post-PVE.…”
Section: Interventional Radiologymentioning
confidence: 99%